Challenges Faced by English Teachers in Indragiri Hulu Regency in Teaching Speaking Through Online Platform - Tarigan, Stevani Likasari; Safryadin, Safryadin; Sofyan, Dedi (ENGLISH FRANCA : Academic Journal of English Language and Education, 2022)
The research aims to investigate the English teacher's challenges in teaching speaking through the online platform when the preparing lesson plan, while the teaching performing, and when the evaluating. This research employed a mixed-method sequential explanatory strategy to reveal the data-oriented to the aforementioned focuses. Fifty-two English teachers engaged as the correspondent of the questionnaire while thirteen English teachers were selected as the participant in the interview. They were selected based on the purposive sampling technique and taken from Senior High Schools in Indragiri Hulu Regency. To gather the data, the questionnaire and interview were deployed and were further analyzed by using the interactive model data analysis. The findings demonstrate that the majority of English teachers had a negative category in teaching speaking through online platforms with an average of total score 122. The challenges when preparing the lesson plan covered four aspects: prepare teaching materials, activity, media, and prepare evaluation materials. Subsequently, the challenges when preparing the lesson plan are the teachers should have not prepared online-based learning media, searched for online speaking topics, and searched for additional teaching materials. Moreover, the lack of internet quota and connection made the students got difficulty joining classes online. In turn, while the teaching performance is teachers difficulty in coping with students' behavior, difficulty in motivating students, and giving example topics on speaking online. Furthermore, in evaluating the teacher's challenges difficulty in assessing student assignments because at the time of online learning students there were only a few students who responded to the teacher. Further studies are expected to seek possible solutions regarding the challenges faced by the teachers in teaching speaking online.